An Automatic Prediction of Solar Radiation for Renewable Energy using Machine Learning models. - Bilal, Blouzi; Noufle Mohammed Hadi, Lalmi (My University, 2022)
As a result of the substantial growth and development of renewable sources of energy, production sources have varied and the network has become more difficult to manage. Therefore, predicting the electricity generated by renew- able sources has become critical. From this point of view, machine learning, which is part of AI, seems to be one of the best ways to achieve this goal. Machine learning techniques are capable of controlling the variations in re- newable energy output and, therefore, facilitate their integration into the energy mix. Thus, one of the major goals of this research is to perform a comprehensive comparison of three prominent machine learning techniques, including support vector regression, linear regression, and random forest, for the short-term prediction of the solar radiation that causes the power produced by photovoltaic solar panels. The dataset we used in this study represents data from the year 2021 and is related to El Hadjira, which is a semi-desert climate province in Algeria. In the testing phase, the results showed that random forest was the most accurate prediction method, with R2=0.334 and RMSE=238.08 W/m2Du fait de la forte croissance et du développement des énergies renouvelables, les sources de production se sont diversifiées et le réseau est devenu plus difficile à gérer. Par conséquent, la prévision de l'électricité produite par des sources renouvelables est devenue critique. De ce point de vue, l'apprentissage automatique, qui fait partie de l'IA, semble être l'un des meilleurs moyens d'atteindre cet objectif. Les techniques de machine learning sont capables de contrôler les variations de production d'énergies renouvelables et donc de faciliter leur intégration dans le mix énergétique. Ainsi, l'un des principaux objectifs de cette recherche est d'effectuer une comparaison complète de trois techniques d'apprentissage automatique de premier plan, y compris la régression vectorielle de support, la régression linéaire et la forêt aléatoire, pour la prédiction à court terme du rayonnement solaire qui provoque l'énergie produite. par des panneaux solaires photovoltaïques. L'ensemble de données que nous avons utilisé dans cette étude représente les données de l'année 2021 et est lié à El Hadjira, qui est une province climatique semi-désertique en Algérie. Lors de la phase de test, les résultats ont montré que la forêt aléatoire était la méthode de prédiction la plus précise, avec R2 = 0,334 et RMSE = 238,08 W/m2.
mémoire mastre inforamtique
Keywords: Solar radiation prediction, Forecasting solar power, Machine learning , Linear regression, Random forest, Support vector regression, Ar- tificial intelligence.; Prédiction du rayonnement solaire, Prévision de l'énergie solaire, Apprentissage automatique, Régression linéaire, Forêt aléatoire, Régression vectorielle de support, Intelligence artificielle.